Evaluation of Educational School Environment and Academic Self-Evaluation of Adolescent Athletes and Non-Athletes (Baltic Journal of Sport and Health Sciences, 2016)
Background. Grigaliūnienė, Vėlavičienė, Šulga, and Keblys (2007) have revealed that meaningful relationships with teachers are influenced by positive attitudes towards them with a good emotional atmosphere in the classroom and a positive microclimate between pupils and teachers. Many scientists point out that education in sports activities positively impacts the development of adolescents’ communication and collaboration with peers and adults, adequate self-evaluation and other positive personality characteristics (Kremer-Sadlik & Kim, 2007; Ream & Rumberger, 2008). Research aim was to determine the evaluation of educational school environment and academic self-evaluation of 11–15-year-old adolescent athletes and non-athletes.Methods. The research was conducted in 2015. We questioned 209 adolescents, aged 11–15 years. In order to determine adolescents’ attitudes towards school educational environment, the survey included the following scales: “Teachers’  help  for  pupils”;  “Support  of  classmates”;  “Positive  relationship  between  adolescents  and  school”; “Attitude towards socioeducational school environment”; “Loneliness at school”, and “Academic self-evaluation”. Results. The survey revealed that boys’ attitudes to socioeducational school environment resulted to be better than  that  of  girls  (p